2009
DOI: 10.1016/j.techsoc.2009.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Access to ICT education for girls and women in rural South Africa: A case study

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 10 publications
(4 reference statements)
0
32
0
1
Order By: Relevance
“…With the exception of two studies focusing on high school girls only (Clayton et al 2012;Dlodlo 2009), these studies compared attitudes of secondary school students based on sex. Of these studies in Table 5B, …”
Section: Studies Of Pre-university Students' Beliefs About It Careersmentioning
confidence: 99%
“…With the exception of two studies focusing on high school girls only (Clayton et al 2012;Dlodlo 2009), these studies compared attitudes of secondary school students based on sex. Of these studies in Table 5B, …”
Section: Studies Of Pre-university Students' Beliefs About It Careersmentioning
confidence: 99%
“…Studies have shown that ICT has proved to be central to the socio-economic development of any nation. This tool, [2] can provide women access to quality education, skill acquisition, expertise and even lifelong learning to be relevant in any field of interest. Parents forbidding their girls access to these tools because of their supposed corrupting influences deprive themselves and their girls of not only their financial benefits and exposure but also limit their potentials for improved productivity, slow down the nation's growth and the chance to compete favorably with her boy-child counterpart in an economy that is fast becoming digital.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, women in rural environments are more vulnerable than those in urban environments. This is not only a problem of morality and equality, but also significant as women is important actors in an ICT context, and have been shown to be of increasing significance to the socio-economic development of any nation (Dlodlo, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of ways to enhance female access to ICT in resource-poor environments. For instance by taking account of women's experiences by allowing these experiences to be shared with others, facilitating ICT access for women, creating an enabling environment for ICT in education, increasing the number of careers in ICT for and by women, and promoting local culture and language (Dlodlo, 2009). Dlodlo's study also stresses the importance of general collaboration in ICT-related activities to pursue common ICT objectives.…”
Section: Introductionmentioning
confidence: 99%